Prison Shakespeare For These Deep Shames and Great Indignities - Pensalfini, Rob.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book explores the development of the global phenomenon of Prison Shakespeare, from its emergence in the 1980s to the present day. It provides a succinct history of the phenomenon and its spread before going on to explore one case study the Queensland Shakespeare Ensemble's (Australia) Shakespeare Prison Project in detail. The book then analyses the phenomenon from a number of perspectives, and evaluates a number of claims made about the outcomes of such programs, particularly as they relate to offender health and behaviour. Unlike previous works on the topic, which are largely individual case studies, this book focuses not only on Prison Shakespeare's impact on the prisoners who directly participate, but also on prison culture and on broader social attitudes towards both prisoners and Shakespeare.
Keywords: British literature; Early Modern/Renaissance Literature; Prison and Punishment; Poetry and Poetics